An economic perspective on payments migration - Anneke Kosse; Zhentong Lu; Gabriel Xerri (Bank of Canada, 2020)
Canada is in the midst of developing three new core payment systems: Lynx, Settlement Optimization Engine (SOE) and Real-Time Rail (RTR). Lynx and SOE will replace the current Large Value Transfer System (LVTS) and Automated Clearing Settlement System (ACSS), whereas RTR will be a new capability. This paper examines the expected migration of ACSS and LVTS payments into RTR, SOE and Lynx. To that end we define a methodology for comparing the current and future payment instruments that end-users will be faced with in the new payments landscape. Similarly, we develop a method to assess the current and future payment systems from the perspective of banks. Based on this we estimate that a substantial portion of the current value of ACSS and LVTS payments might find its way to RTR due to changing end-user behaviour. Our analysis also suggests that banks might migrate a considerable amount of LVTS transactions to either SOE or RTR. The findings provide a good starting point for future research on the implications of the new payments infrastructure.
Keywords: E42; G; G2; G21; 330; Payment clearing and settlement systems; Financial services; Financial system regulationand policies